2001
DOI: 10.1037/0002-9432.71.3.374
|View full text |Cite
|
Sign up to set email alerts
|

Attachment style classification and posttraumatic stress disorder in former prisoners of war.

Abstract: Adult attachment style and post-traumatic stress disorder (PTSD) symptomatology were investigated in 107 former prisoner of war veterans. Those with secure attachment styles scored significantly lower on measures of PTSD than did those with insecure styles, and attachment style was a stronger predictor of PTSD symptom intensity than was trauma severity. The suggested association between attachment style and PTSD's development and persistence are discussed in relation to research and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 27 publications
6
68
0
Order By: Relevance
“…As neither the 'dose-effect curve' hypothesis nor aspects that are specific to the type of CI could fully account for this, research oriented itself towards subjective factors. The assumption is that subjective factors moderate between a CI and the development of a PTSD (Dieperink, Leskela, Thuras, & Engdahl, 2001;Marmar et al, 1999;Spitzer et al, 2000). A subjective factor that has been the object of several studies is adult attachment.…”
Section: Introductionmentioning
confidence: 99%
“…As neither the 'dose-effect curve' hypothesis nor aspects that are specific to the type of CI could fully account for this, research oriented itself towards subjective factors. The assumption is that subjective factors moderate between a CI and the development of a PTSD (Dieperink, Leskela, Thuras, & Engdahl, 2001;Marmar et al, 1999;Spitzer et al, 2000). A subjective factor that has been the object of several studies is adult attachment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one candidate variable that is likely to be associated with PTSD symptoms and academic burnout is parental attachment (Aspelmeier, Elliott, & Smith, 2007; Duchesne & Larose, 2007; Han, 2006). Lack of stress-reducing secure attachment often results in PTSD in adolescents (Benoit, Bouthillier, Moss, Rousseau, & Brunet, 2010; Dieperink, Leskela, Thuras, & Engdahl, 2001). Many researchers have theorized and investigated parental attachment as a resiliency factor for traumatized children and adolescents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, attachment insecurity may predispose a traumatized person to PTSD. Although this sequence of events and the direction of causality of the attachment-PTSD link have not been directly examined, numerous studies have found that attachment insecurities are associated with PTSD, regardless of the type or severity of the traumatic event (e.g., Dieperink, Leskela, Thuras, & Engdahl, 2001;Fraley, Fazzari, Bonanno, & Dekel, 2006;Muller & Lemieux, 2000). In an earlier study of the cohort of ex-POWs from the 1973 Yom Kippur War that we are examining in the present study, Solomon, Ginzburg, Mikulincer, Neria, and Ohry (1998) found that anxious attachment was associated with more severe PTSD symptoms even 20 years after the war.…”
Section: Attachment Insecurities Ptsd and Stsmentioning
confidence: 99%